To solve the equation, we first need to find a common denominator for the fractions on both sides.
The equation is: (-2)/(x + 4) = 4/(x + 3)
Multiply the left side by (x + 3) and the right side by (x + 4) to get:
(-2)(x + 3) = 4(x + 4)
Expand the left side:
-2x - 6 = 4x + 16
Now, move all the x terms to one side and the constant terms to the other side:
-2x - 4x = 16 + 6
-6x = 22
Divide by -6 to solve for x:
x = -22/6
x = -11/3 or -3 2/3
Therefore, the correct solution is -11/3 or -3 2/3. Let's check this solution now.
(-2)/(-11/3 + 4) = 4/(-11/3 + 3)
(-2)/(-11/3 + 12/3) = 4/(-11/3 + 9/3)
(-2)/(1/3) = 4/(-2/3)
-6 = -6
The solution checks out, so the correct answer is -11/3.
Solve the equation. Check the solution.
negative two over x plus four equals four over x plus three
(1 point)
Responses
negative thirteen over six
Image with alt text: negative thirteen over six
–11
–11
negative eight over three
Image with alt text: negative eight over three
negative eleven over three
1 answer